Therapeutic Effect of the Substrate-Selective COX-2 Inhibitor IMMA in the Animal Model of Chronic Constriction Injury - Jones, Melissa; Wen, Jie; Selvaraj, Prabhuanand; Tanaka, Mikiei; Moran, Sean; Zhang, Yumin (Frontiers in Pharmacology, 2018)
Enhancement of endocannabinoid signaling has emerged as an attractive strategy for the treatment of pain. In addition to the well-characterized hydrolytic pathways, cyclooxygenase-2 (COX-2) mediated oxygenation is thought to be an alternative route for endocannabinoid metabolism and therefore provides a new avenue for drug intervention. In this study, we examined the therapeutic effect of indomethacin morpholinamide (IMMA), a novel substrate-selective COX-2 inhibitor, in the chronic constriction injury (CCI) mouse model. Treatment with IMMA significantly alleviated hyperalgesia and mechanical allodynia demonstrated by increased thermal withdrawal latency in Hargreaves test and tactile thresholds in Von Frey test. Accumulation of astrocytes and microglia in spinal cord dorsal horn and infiltration of macrophages into the dorsal root ganglion and sciatic nerve were reduced by drug treatment. Co-administration of the CB2 receptor antagonist, but not the CB1 receptor antagonist partially reversed the inhibitory effect of IMMA on pain sensitivity and inflammatory infiltrates. IMMA downregulated the mRNA expression of TNF-α and IL-1β and the production of IL-6 and MCP-1 proteins in the ipsilateral sciatic nerve. The enhanced NF-κB DNA binding activity in the CCI mouse dorsal spinal cord was also significantly reduced, suggesting that inactivation of NF-κB contributes to the anti-inflammatory property of IMMA. However, different from the previous reports showing that IMMA can increase endocannabinoids without interfering with arachidonic acid metabolism, treatment with IMMA failed to elevate the endogenous levels of AEA and 2-AG, but significantly reduced the production of prostaglandin E2 (PGE2). Furthermore, the mRNA expression of enzymes involved in PGE2 production, COX-2 and prostaglandin E synthase 2 in the ipsilateral sciatic nerve was also suppressed by IMMA treatment. Taken together, these results suggested that IMMA might exert anti-nociceptive effects through multiple mechanisms which include, but are not limited to, CB2 receptor activation and reduced PGE2 production.